Pengaruh Personal Branding Vincent Desta dan Guerilla Marketing terhadap Brand Image: Studi Kasus Instagram Vindes Store - Aulia Zahra; Adam Hermawan; Btari Mariska Purwaamijaya (Jurnal Transformasi Bisnis Digital, 2024)
This research aims to determine the influence of Vincent Desta's personal branding by looking at the concept of guerilla marketing as a marketing element on the brand image on the Vindes Store Instagram. This research data was obtained from the results of distributing questionnaires with a population sample of 190 respondents processed using SPSS. The findings of this research show that there is a positive influence of the personal branding variable on brand image partially, the guerilla marketing variable also has a positive influence on brand image partially, the personal branding and guerilla marketing variables have a simultaneous influence on brand image with an R - Square value amounting to 14.7% with the variability of brand image being explained by personal branding and guerilla marketing.